Analysis of Scientific Literacy Ability Junior High School Students in Science Learning on Environmental Pollution - Inggrid Ayu Amala; Sutarto Sutarto; Pramudya Dwi Aristya Putra; Indrawati Indrawati (Postgraduate, University of Mataram, 2023)
The development of science in the 21st century science has an important role, especially natural science. Scientific developments in the field of education require students to have skills that will continue to be used to improve the quality of human resources. One of the skills needed is scientific literacy skills which are important for students to have because they can make students not only memorize subject matter but can make students able to understand and analyze science concepts and processes that occur contextually. Scientific literacy has indicator aspects namely explaining phenomena scientifically, evaluating and designing scientific investigations, and interpreting data and evidence scientifically. This research is descriptive research. Research subjects of grade 8 students in the academic year 20 21/2022. The purpose of this study was to analyze the scientific literacy abilities of SMPIT Al-Ghozali students in science learning on environmental pollution. Data collection techniques used scientific literacy tests with reference to aspects of scientific literacy indicators and interviews. The results showed that students' scientific literacy achievement was 54.14% with sufficient criteria and the highest achievement indicator was 60% in the aspect of the indicator explaining phenomena scientifically. The results of this study indicate that students' scientific literacy needs to be improved in science learning activities